2007
DOI: 10.1038/sj.jes.7500589
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin in maternal breast milk and newborn head circumference

Abstract: Dioxins are known to affect infant growth and neurodevelopment in both humans and animals. In this study, we examined the relationship between neonatal head circumference, which is related to fetal brain development, and the concentration of dioxins in breast milk as an indicator of maternal exposure. A total of 42 milk samples were obtained on the fifth to eighth postpartum day from mothers in Japan exposed to dioxins in the environment. The levels of seven dioxins and 10 furan isomers were measured in each m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…A previous Finnish study reported that the 2,3,7,8-TCDD, 1,2,3,7,8-PeCDD, and 2,3,4,7,8-PeCDF levels in breast milk were negatively correlated with birth weight (Vartiainen et al, 1998). However, another Japanese study reported that there were significant relationships between infant head circumference and 2,3,7,8-TCDD and 2,3,4,7,8-PeCDF levels (Nishijo et al, 2008). We found significantly negative associations between 2,3,4,7,8-PeCDF levels and birth weight after we adjusted for potential confounders.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…A previous Finnish study reported that the 2,3,7,8-TCDD, 1,2,3,7,8-PeCDD, and 2,3,4,7,8-PeCDF levels in breast milk were negatively correlated with birth weight (Vartiainen et al, 1998). However, another Japanese study reported that there were significant relationships between infant head circumference and 2,3,7,8-TCDD and 2,3,4,7,8-PeCDF levels (Nishijo et al, 2008). We found significantly negative associations between 2,3,4,7,8-PeCDF levels and birth weight after we adjusted for potential confounders.…”
Section: Discussionmentioning
confidence: 77%
“…Another recent study examining the effects of individual congeners of PCDDs/PCDFs and DL-PCBs on birth weight reported that only OCDD levels in breast milk had a significant negative correlation (Tajimi et al, 2005). However, there were no significant relationships between birth weight and PCDDs/PCDFs congeners in maternal breast milk (Nishijo et al, 2008). Thus, reported results on the relationship between birth weight and the levels of PCDDs/PCDFs and DL-PCBs are currently limited and inconsistent.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Breast milk samples were analyzed following previously reported procedures (Tawara et al 2003;Nishijo et al 2008). The fat content in breast milk was determined using the method described by Patterson et al (1987 Berg et al 2006).…”
Section: Analysis Of Dioxin In Breast Milkmentioning
confidence: 99%